Global trends and hotspots in exercise therapy for insomnia research: bibliometric and visual analysis - Li, Liang; Liang, Jiuzhu; Fan, Tonggang (Frontiers in Neurology, 2025)
ObjectiveThis study analyzes trends and hotspots in the research on exercise for insomnia using bibliometric methods and visually presents key information in the field.MethodsUsing Web of Science Core Collection as a source of literature, Microsoft Excel 2019, CiteSpace, VOSviewer, and the Bibliometrix package based on R language software were used to create visualization graphs and analyze the publications by country and region, institution, journal, author, reference, and keyword.ResultsThis study included 1,419 papers. The overall number of publications showed an increasing trend, and the highest number of papers in this field were published by the United States and China by country, the University of California System in the United States by institution, and Markus Gerber from Switzerland by author. The trends and hotspots in this field identified through keyword analysis include “insomnia,” exercise,” “depression,” “older adults,” and “quality of life.”ConclusionThe research field of exercise therapy for insomnia is receiving increasing attention, and this study provides a clear and intuitive reference for researchers.